“Ekphrasis of St. Sophia” by Paul the Silentiary and the Earlier Poetic Tradition - Tatiana L. Aleksandrova (Studia Litterarum)
The purpose of this paper is to trace poetic samples that Paul the Silentiary borrowed for his poems “Ekphrasis of St. Sophia” and “Ekphrasis of the Ambo” and to explore the work of the poet with the texts of his predecessors. From the point of form, the poem by Paul is a mixture of the ekphrasis and encomium, addressed to the Emperor Justinian as the founder of St. Sophia Cathedral. Paul the Silentiary follows the tradition of the Greek epic and relies on the various samples of encomiastic poetry, not only Greek but also Latin. The influence of Gregory the Theologian is also noticeable. The article dwells on several examples of Paul’s usage of poetic formulas, borrowed from other poets, and discusses techniques of narration. Special attention is paid to the parallels between the “Ekphrasis” and “Silvae” by Statius: both poets similarly use the rhetorical device of prosopopeia and ethopeia, both introduce the mythical figure of the protagonist’s interlocutor; both similarly and almost in the same terms describe different kinds of marble; both have similar expressions. Despite the fact that part of the described coincidences have analogues in Hellenistic poetry, it appears that direct use of “Silvae” by Paul is quite plausible, because in the Late Antiquity, Statius was studied at school.